Molecular characterization of circulating tumor cells from patients with metastatic breast cancer reflects evolutionary changes in gene expression under the pressure of systemic therapy - Aaltonen, Kristina E; Novosadová, Vendula; Bendahl, Pär-Ola; Graffman, Cecilia; Larsson, Anna-Maria; Rydén, Lisa (Oncotarget, 2017)
Resistance to systemic therapy is a major problem in metastatic breast cancer (MBC) that can be explained by initial tumor heterogeneity as well as by evolutionary changes during therapy and tumor progression. Circulating tumor cells (CTCs) detected in a liquid biopsy can be sampled and characterized repeatedly during therapy in order to monitor treatment response and disease progression.Our aim was to investigate how CTC derived gene expression of treatment predictive markers (ESR1/HER2) and other cancer associated markers changed in patient blood samples during six months of first-line systemic treatment for MBC. CTCs from 36 patients were enriched using CellSearch (Janssen Diagnostics) and AdnaTest (QIAGEN) before gene expression analysis was performed with a customized gene panel (TATAA Biocenter).Our results show that antibodies against HER2 and EGFR were valuable to isolate CTCs unidentified by CellSearch and possibly lacking EpCAM expression. Evaluation of patients with clinically different breast cancer subgroups demonstrated that gene expression of treatment predictive markers changed over time. This change was especially prominent for HER2 expression.In conclusion, we found that changed gene expression during first-line systemic therapy for MBC could be a possible explanation for treatment resistance. Characterization of CTCs at several time-points during therapy could be informative for treatment selection.
Keywords: receptory pro estrogeny; regulace genové exprese u nádorů; Humans; lidé středního věku; gene expression; Disease Progression; Biomarkers, Tumor; circulating tumor cells; Female; Aged; dospělí; Neoplastic Cells, Circulating; receptor erbB-2; senioři; lidé; chemorezistence; nádorové biomarkery; Adult; Breast Neoplasms; Neoplasm Metastasis; metastázy nádorů; staging nádorů; ženské pohlaví; Kaplanův-Meierův odhad; Receptors, Estrogen; Middle Aged; stanovení celkové genové exprese; transkriptom; nádorové cirkulující buňky; Aged, 80 and over; Receptor, ErbB-2; human epidermal growth factor receptor 2 (HER2); Estrogen receptor (ER); nádory prsu; Transcriptome; metastatic breast cancer; senioři nad 80 let; progrese nemoci; Kaplan-Meier Estimate; Neoplasm Staging; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Drug Resistance, Neoplasm